Implementation Of Individual Supervision Techniques As The Implementation Of Supervision Work In SDN 009 Sub-District Tambusai, Rokan Hulu Regency - Saibatul Aslamiah (STKIP Rokania Pasir Pangaraian, 2022)
Improving the quality of learning in schools is highly dependent on several factors. A very important factor, among others, is the implementation of improving the professionalism of quality improvement teachers. School supervisors are one of the partners of teachers in improving the quality of education, from that one of the school supervisors' efforts to improve quality in their target schools is to carry out individual supervision, a positive thing that must be carried out in schools, especially for new teachers, must be improved by supervisors. so that it supports quality problems, including in class attendance in the teaching and learning process. To improve the quality of teachers, efforts can be made in various ways, one of which is individual supervision carried out in class at SDN 009 Tambusai.